2020
DOI: 10.1007/s12529-019-09843-x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Alpha-Amylase as a Biomarker of Stress in Behavioral Medicine

Abstract: In recent years, research in behavioral medicine has become increasingly focused on understanding how chronic and acute exposure to stress impacts health outcomes. During stress, the body's physiological stress systems are activated. These systems closely interact with the immune system and are, thus, importantly implicated in the onset and maintenance of disease states. While much of the research in behavioral medicine that has investigated the effects of stress on disease has focused on the role of the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
124
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 52 publications
1
124
0
4
Order By: Relevance
“…Alpha-amylase is an enzyme that cleaves large alpha-linked polysaccharides into glucose and maltose to be used as immediate energy sources. While alpha-amylase is not technically a biomarker, literature in recent years has shown that high levels of salivary alpha-amylase may indicate chronic stress ( Nater and Rohleder, 2009 ; Vineetha et al, 2014 ; Steckl and Ray, 2018 ; Ali and Nater, 2020 ). The confirmation of salivary alpha-amylase as a reliable biomarker for stress will allow for greater variability in stress quantification approaches through saliva samples.…”
Section: How To Measure Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha-amylase is an enzyme that cleaves large alpha-linked polysaccharides into glucose and maltose to be used as immediate energy sources. While alpha-amylase is not technically a biomarker, literature in recent years has shown that high levels of salivary alpha-amylase may indicate chronic stress ( Nater and Rohleder, 2009 ; Vineetha et al, 2014 ; Steckl and Ray, 2018 ; Ali and Nater, 2020 ). The confirmation of salivary alpha-amylase as a reliable biomarker for stress will allow for greater variability in stress quantification approaches through saliva samples.…”
Section: How To Measure Stressmentioning
confidence: 99%
“…Cortisol is a glucocorticoid hormone, whose release is controlled by the central nervous system, more specifically the HPA axis. Cortisol is currently considered the gold standard for evaluating the activity of the HPA axis ( Ali and Nater, 2020 ). Glucocorticoids are responsible for reallocation of energy to overcome real or anticipated stressors perceived during stress response ( Herman et al, 2016 ).…”
Section: How To Measure Stressmentioning
confidence: 99%
“…Diurnal salivary stress biomarkers We will focus on two salivary stress biomarkers. These include salivary cortisol, as a downstream marker of HPA activity, and salivary α-amylase (sAA), as a proxy measure of SAM activation; they can be measured concomitantly [57] and together offer a comprehensive view of physiological stress, as differing diagnostic and treatment effects have been observed between these markers [58]. Both salivary cortisol and sAA follow a distinct diurnal rhythm: cortisol levels peak approximately 30 min after awakening and decrease throughout the day, whereas sAA has a pronounced decline after awakening followed by an increase across the day [57].…”
Section: Biological Assessmentsmentioning
confidence: 99%
“…Lower anabolic balance is associated with more unfavorable psychological well-being and health outcomes [14,15]. SAA is an enzyme secreted from the salivary glands that has been increasingly used as a marker of the activity of the sympathoadrenal-medullary (SAM) axis, another important regulatory system involved in the response to psychosocial stressors [16][17][18]. Researchers have not investigated cardiovascular differences as a function of general MPA level other than for HR and HR variability (HRV) [8].…”
Section: Introductionmentioning
confidence: 99%